2011
DOI: 10.1186/1471-2407-11-196
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative medicine use in oncology: A questionnaire survey of patients and health care professionals

Abstract: BackgroundWe aimed to investigate the prevalence and predictors of Complementary and Alternative Medicine (CAM) use among cancer patients and non-cancer volunteers, and to assess the knowledge of and attitudes toward CAM use in oncology among health care professionals.MethodsThis is a cross-sectional questionnaire survey conducted in a single institution in Ireland. Survey was performed in outpatient and inpatient settings involving cancer patients and non-cancer volunteers. Clinicians and allied health care p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
75
5
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 34 publications
12
75
5
6
Order By: Relevance
“…Among the healthcare professionals who had participated in the study, nurses were those who granted less importance to the knowledge of NCT. As far as Reiki is http://dx.doi.org/10.15405/epsbs.2017.06.11 Corresponding Author: Rosa Martins Selection and peer-review under This study is in agreement with the one conducted by Chang et al (2011) that indicated that 58.8% of healthcare professionals confess that they didn't have the proper knowledge and that 79.2% of them are not aware of the relevance of the use of NCT in oncological units. Brown et al (2007) had found out that the healthcare professionals who had participated in his study had limited knowledge and little experience with NCT, thus feeling unprepared to talk with their patients about these therapies.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Among the healthcare professionals who had participated in the study, nurses were those who granted less importance to the knowledge of NCT. As far as Reiki is http://dx.doi.org/10.15405/epsbs.2017.06.11 Corresponding Author: Rosa Martins Selection and peer-review under This study is in agreement with the one conducted by Chang et al (2011) that indicated that 58.8% of healthcare professionals confess that they didn't have the proper knowledge and that 79.2% of them are not aware of the relevance of the use of NCT in oncological units. Brown et al (2007) had found out that the healthcare professionals who had participated in his study had limited knowledge and little experience with NCT, thus feeling unprepared to talk with their patients about these therapies.…”
supporting
confidence: 78%
“…Chang et al (2011), for instance, tell us that 80% of the pharmacists, 49.2% of the nurses, 37.0% of the physiotherapists and 28.8% of the doctors who had participated in the study had already sought NCT treatments. These researchers gathered in the same study oncological patients, volunteers who didn't suffer from any oncological disease and healthcare workers (who were involved in the treatment of patients who were suffering from cancer) and found values of prevalence in the adherence to NCT (29.1%,30.9% and 39.7 %respectively) in which the healthcare workers show higher values than the users/patients.…”
mentioning
confidence: 99%
“…And also same results are taken from pediatric intensive care patients, chronic other patients, hospice patients and their health professionals, too (Demmer and Sauer, 2002;Bouhairie et al, 2006;Mathur et al, 2008;Loewy et al, 2013). Chang et al (2011) research complementary and alternative medicines in patients, healthy people and health professionals via a survey and this cohort study shows us that music therapy is not preferable very much. Only 8% of participants refer music therapy in this study and more referable ones are more popular and expensive methods like natural supplements, green tea, massage, herbal remedies (Chang et al, 2011).…”
Section: Discussionmentioning
confidence: 60%
“…Chang et al (2011) research complementary and alternative medicines in patients, healthy people and health professionals via a survey and this cohort study shows us that music therapy is not preferable very much. Only 8% of participants refer music therapy in this study and more referable ones are more popular and expensive methods like natural supplements, green tea, massage, herbal remedies (Chang et al, 2011).…”
Section: Discussionmentioning
confidence: 89%
“…For example, it has been reported that media coverage of CAM is inconsistent [29], and studies have argued for the need for increased awareness about potential harms and benefits [55]. Thus, we also investigated the extent to which harms and benefits were reported.…”
Section: Aim 3 Harms Benefits and Website Purposementioning
confidence: 99%